Developing Narrative Flashcards Based on Education Through Art to Improve Elementary Students’ Learning Outcomes on Food Chains - Azzahro, Ilma; Ary, Deasylina da (Universitas Islam Negeri Raden Intan Lampung, 2026)
Appropriate instructional media are central to supporting elementary students’ conceptual understanding in science learning, particularly when the content requires learners to reason about invisible ecological relationships. This study developed and evaluated narrative flashcards based on the Education Through Art approach for fifth-grade instruction on food chains. A research and development design using the ADDIE model was employed. The participants were 22 fifth-grade students at SDN Kalijambe 01, Tarub, Tegal, Indonesia, together with one media expert, two material experts, one teacher, and student respondents involved in product validation and classroom implementation. Data were collected through expert-validation sheets, teacher and student response questionnaires, classroom observation, interviews, documentation, and pre-test and post-test learning-outcome measures. Descriptive percentage analysis was used to examine feasibility and practicality, while a paired-sample t-test and normalized gain analysis were used to examine learning improvement. The media expert validation score was 86.67%, while the two material expert scores were 88.57% and 92.38%, indicating that the product met very valid criteria. Teacher and student responses also indicated high practicality, with percentages of 88.57% and 83.81%, respectively. Students’ learning outcomes improved significantly after using the media, t(21) = -6.668, p < .001, with a mean gain of 18.64 points and an N-gain score of 0.3266, categorized as a moderate improvement. These findings suggest that narrative flashcards integrating visual art, storytelling, and ecological sequencing can support more meaningful and engaging food-chain learning in elementary science classrooms.